Transport Network Analysis Of Ahmednagar District, Maharashtra State, India (International Journal of Food and Nutritional Sciences, 2022)
The development of transport greatly helps the socio-economic development of a region. The greater the density of transport network in a geographical region, the greater the socio-economic development. Studies have been done regarding their length in Ahmednagar district. For this study, the information about the length of the roads has been taken from the secondary material. The information is from 2017 2019. At the same time, a comparative study of roads in Ahmednagar district of India, Maharashtra has been done.